Controlled Growth of Ag Nanocrystals in a H‐Bonded Open Framework. Issue 60 (2nd October 2019) - Khodja, Walid; Collière, Vincent; Kahn, Myrtil L.; Roques, Nans; Sutter, Jean‐Pascal
Abstract: A procedure that enabled rational access to the first example of hybrid material made of NPs grown within a H‐bonded framework is reported. To avoid competitive reactions with the framework units, the metal precursor was chemically trapped in the porous structure and subsequently photo‐reduced to afford the hybrid material Ag@SPA‐2, which consists of Ag NPs of nanometric sizes (<15 nm) homogeneously distributed in the crystals of the host material. In a subsequent step, taking advantage of the porous matrix the silver NPs have been transformed in situ to Ag2 S NP by simple infiltration of H2 S. The supramolecular network is shown to play an important role in stabilizing the inorganic nanomaterials and thus in controlling their growth. Abstract : Access to a hybrid material made of NPs grown within a H‐bonded framework is reported. The metal precursor was chemically trapped in the porous structure and subsequently photo‐reduced to afford Ag NPs of nanometric sizes (<15 nm) homogeneously distributed in the crystals of the host material. In a subsequent step, taking advantage of the porous matrix, the silver NPs have been transformed in situ to Ag2 S NPs by reaction with H2 S.